2009
DOI: 10.1038/ni.1683
|View full text |Cite|
|
Sign up to set email alerts
|

Hypoxia-inducible factor–dependent induction of netrin-1 dampens inflammation caused by hypoxia

Abstract: The neuronal guidance molecule netrin-1 is linked to the coordination of inflammatory responses. Given that mucosal surfaces are particularly prone to hypoxia-elicited inflammation, we sought to determine the function of netrin-1 in hypoxia-induced inflammation. We detected hypoxia-inducible factor 1alpha (HIF-1alpha)-dependent induction of expression of the gene encoding netrin-1 (Ntn1) in hypoxic epithelia. Neutrophil transepithelial migration studies showed that by engaging A2B adenosine receptor (A2BAR) on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
425
1
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 370 publications
(458 citation statements)
references
References 48 publications
29
425
1
3
Order By: Relevance
“…This finding was corroborated by the lack of RGM-A expression by two well-established endothelial cell lines, human dermal microvascular endothelial cell 1 (HMEC-1) and human umbilical vein endothelial cell (HUVEC) (Fig. 2D) (8).…”
Section: Rgm-a Is Expressed Outside the Cnssupporting
confidence: 49%
See 2 more Smart Citations
“…This finding was corroborated by the lack of RGM-A expression by two well-established endothelial cell lines, human dermal microvascular endothelial cell 1 (HMEC-1) and human umbilical vein endothelial cell (HUVEC) (Fig. 2D) (8).…”
Section: Rgm-a Is Expressed Outside the Cnssupporting
confidence: 49%
“…Appropriate adjusted leukocyte migration and recruitment to the inflammatory site is essential to control inflammation for effective host defense and also to avoid tissue damage due to an aberrant, exacerbated inflammatory response (3,4). To test whether RGM-A is a chemorepulsive cue for PMN migration in vitro, we applied formyl-methionyl-leucyl-phenylalanine (fMLP)-induced chemotaxis using a paracellular flux assay (8). On stimulation by fMLP, granulocytes migrate across a semipermeable membrane seeded with epithelial CaCo cells, forming a cell monolayer (Fig.…”
Section: Rgm-a Reduces Pmn Migration Through the Neogenin Receptor Inmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the anti-inflammatory protein netrin-1 was shown to be regulated by both NF!B [42] and HIF [43]. We speculate that this duality in the transcriptional crosstalk for regulating both pro-and anti-inflammatory genes might be dependent on other factors in order to resolve inflammation.…”
Section: Discussionmentioning
confidence: 92%
“…With identification of the newer roles for netrin-1 other than its involvement in nervous system development, research is currently focused on understanding the mechanism of netrin-1 induction. More recent studies have reported the critical role of hypoxia inducible factor-1a (Hif-1a) in regulating endogenous netrin-1 expression [23]. Transcription factor Hif-1a is translocated into the cell nuclei in response to tissue hypoxia where it regulates expression of a plethora of genes that help cellular and tissue responses to low oxygen presence to maintain oxygen homeostasis in the biological system [24][25][26].…”
Section: Netrin-1 Gene Delivery To the Heartmentioning
confidence: 99%